The Aftermath of 9/11: The Shift of Islam Representation in American TV Series FBI - El Sarah, Ratu Nadhirah; Adi, Ida Rochani (Rubikon : Journal of Transnational American Studies, 2024)
The conflict surrounding Islam has been going on for many years, even before the September 11th, 2001 (henceforth, 9/11) incident occurred. However, the fact that the post-incident living circumstances for Muslim people especially in America has been undeniably rough, raises a new trend where Islam is being represented poorly and almost always talked about in negative ways. There are certain characteristics which are attributed especially to identify Muslims, and also certain role that they play in media. Using the Representation theory proposed by Stuart Hall, this research aims to uncover how Islam is represented in American TV series, FBI, which might be seen as a reflection of how Muslims are living in the United States post-9/11 incident. The result found that in the FBI series, Islam is still mainly represented as Arab people, though in reality not every Arabs are Muslims, but the point of view has been slightly shifted for the better. The findings highlight the changing dynamics of Muslim representation, driven by the evolving Muslim community and market demands, contributing to a more nuanced understanding of cultural shifts in the representation of Islam.